Assessment of the earthquake hazard and zoning of associated environmental hazards in the Borujerd area, Lorestan province - Siamak Baharvand; Vahab Amiri Amraei; Salman Soori (مخاطرات محیط طبیعی, 2020)
The Iranian plateau is a vast area of pressure throughout the alpine-Himalayan orogenic belt, that with the continuous movement of the plates in this area, we encounter the seismic activity in most parts of Iran. In this research, investigation of the tectonic earthquake and earthquake hazard analysis has been considered using a deterministic method and study of the active fault lines in Boroujerd city in the north of Lorestan province. The main objective of the study is to confront the risk of earthquakes by identifying the maximum magnitude and maximum horizontal acceleration of the earth for the active faults lines of the area and also analyzing and zoning the environmental hazards associated with this phenomenon. For this purpose, the main faults lines of the area were identified by using the satellite imagery, the geological map and field studies and then, the earthquake with the most probability was determined by using the definitive method of the earthquake plan, and using the existing empirical relationships among the earthquake characteristics. Based on the calculations, the magnitude of the earthquakes caused by the main faults in this area ranged between 6.17 to 7.07 Gal and the peak ground acceleration (PGA) based on the Donovan and Campbell methods were 0.308 and 0.321 Gal. Studies showed that the two phenomena of liquefaction and landslide are the most important environmental hazards after the earthquake occurrence in Boroujerd area. In this research, liquefaction hazard zoning and landslide hazard maps are provided based on seismic-geotechnical hazards zoning guidelines and fuzzy logic methods. Then, by integrating liquefaction and landslide hazard maps, the map of environmental hazards has been prepared. Based on the results, 12.9, 25.6, 24.8, 17.6, and 19.1 percent of the area are in very low, moderate, high and very high-risk classes, respectively.